Scales of memory constitutional justice and historical evil - Collings, Justin (Oxford, United Kingdom Oxford University Press, 2021)
This book explores the relationship between constitutional interpretation and the memory of historical evil. Specifically, it examines how the constitutional courts of the United States, Germany, and South Africa have grappled, respectively, with the legacies of slavery, Nazism, and apartheid.
Introduction : Constitutional Justice and Collective Memory -- A Century of Lost Time: 1865-1954 -- After Brown -- After Hitler: 1951-1975 -- Forever in Hitler's Shadow? : the Court Since 1975 -- South Africa's First Constitutional Court: 1995-2005 -- Chasing Rainbows : 2005-2020 -- Conclusion : Memory in the Balance.
Includes bibliographical references (pages 317-327) and index.
Specialized.
Keywords: Apartheid -- Electronic books -- South Africa; Constitutional history -- Germany; Constitutional history -- South Africa; Constitutional history -- United States; National socialism -- Germany; Slavery -- Law and legislation -- United States